Principles guiding embryo selection following genome-wide haplotyping of preimplantation embryos - Dimitriadou, Eftychia; Melotte, Cindy; Debrock, Sophie; Esteki, Masoud Zamani; Dierickx, Kris; Voet, Thierry; Devriendt, Koen; de Ravel, Thomy; Legius, Eric; Peeraer, Karen; Meuleman, Christel; Vermeesch, Joris Robert (Human reproduction (Oxford), 2017)
Abstract STUDY QUESTION How to select and prioritize embryos during PGD following genome-wide haplotyping? SUMMARY ANSWER In addition to genetic disease-specific information, the embryo selected for transfer is based on ranking criteria including the existence of mitotic and/or meiotic aneuploidies, but not carriership of mutations causing recessive disorders. WHAT IS KNOWN ALREADY Embryo selection for monogenic diseases has been mainly performed using targeted disease-specific assays. Recently, these targeted approaches are being complemented by generic genome-wide genetic analysis methods such as karyomapping or haplarithmisis, which are based on genomic haplotype reconstruction of cell(s) biopsied from embryos. This provides not only information about the inheritance of Mendelian disease alleles but also about numerical and structural chromosome anomalies and haplotypes genome-wide. Reflections on how to use this information in the diagnostic laboratory are lacking. STUDY DESIGN, SIZE, DURATION We present the results of the first 101 PGD cycles (373 embryos) using haplarithmisis, performed in the Centre for Human Genetics, UZ Leuven. The questions raised were addressed by a multidisciplinary team of clinical geneticist, fertility specialists and ethicists. PARTICIPANTS/MATERIALS, SETTING, METHODS Sixty-three couples enrolled in the genome-wide haplotyping-based PGD program. Families presented with either inherited genetic variants causing known disorders and/or chromosomal rearrangements that could lead to unbalanced translocations in the offspring. MAIN RESULTS AND THE ROLE OF CHANCE Embryos were selected based on the absence or presence of the disease allele, a trisomy or other chromosomal abnormality leading to known developmental disorders. In addition, morphologically normal Day 5 embryos were prioritized for transfer based on the presence of other chromosomal imbalances and/or carrier information. LIMITATIONS, REASONS FOR CAUTION Some of the choices made and principles put forward are specific for cleavage-stage-based genetic testing. The proposed guidelines are subject to continuous update based on the accumulating knowledge from the implementation of genome-wide methods for PGD in many different centers world-wide as well as the results of ongoing scientific research. WIDER IMPLICATIONS OF THE FINDINGS Our embryo selection principles have a profound impact on the organization of PGD operations and on the information that is transferred among the genetic unit, the fertility clinic and the patients. These principles are also important for the organization of pre- and post-counseling and influence the interpretation and reporting of preimplantation genotyping results. As novel genome-wide approaches for embryo selection are revolutionizing the field of reproductive genetics, national and international discussions to set general guidelines are warranted. STUDY FUNDING/COMPETING INTEREST(S) The European Union's Research and Innovation funding programs FP7-PEOPLE-2012-IAPP SARM: 324509 and Horizon 2020 WIDENLIFE: 692065 to J.R.V., T.V., E.D. and M.Z.E. J.R.V., T.V. and M.Z.E. have patents ZL910050-PCT/EP2011/060211-WO/2011/157846 (‘Methods for haplotyping single cells’) with royalties paid and ZL913096-PCT/EP2014/068315-WO/2015/028576 (‘Haplotyping and copy-number typing using polymorphic variant allelic frequencies’) with royalties paid, licensed to Cartagenia (Agilent technologies). J.R.V. also has a patent ZL91 2076-PCT/EP20 one 3/070858 (‘High throughout genotyping by sequencing’) with royalties paid. TRIAL REGISTRATION NUMBER N/A.